Effect of DHCR7 on adipocyte differentiation in goats - Zhibin Li; Tingting Hu; Ruiwen Li; Jinlan Li; Youli Wang; Yanyan Li; Yaqiu Lin; Yong Wang; Xing Jiani (Animal Biotechnology)
Cholesterol is regarded as a signaling molecule in regulating the metabolism and function of fat cells, in which 7-Dehydrocholesterol reductase (DHCR7) is a key enzyme that catalyzes the conversion of 7-dehydrocholesterol to cholesterol, however, the exact function of DHCR7 in goat adipocytes remains unknown. Here, the effect of DHCR7 on the formation of subcutaneous and intramuscular fat in goats was investigated in vitro, and the result indicated that the mRNA level of DHCR7 showed a gradual downward trend in subcutaneous adipogenesis, but an opposite trend in intramuscular adipogenesis. In the process of subcutaneous preadipocytes differentiation, overexpression of DHCR7 inhibited the expression of adipocytes differentiation marker genes (CEBP/α, CEBP/β, SREBP1 and AP2), lipid metabolism-related genes (AGPAT6, FASN, SCD1 and LPL), and the lipid accumulation. However, in intramuscular preadipocyte differentiation, DHCR7 overexpression showed a promoting effect on adipocyte differentiation marker genes (CEBP/α, CEBP/β, PPARγ and SREBP1) and lipid metabolism-related genes (GPAM, AGPAT6, DGAT1 and SCD1) expression, and on lipid accumulation. In summary, our work demonstrated that DHCR7 played an important role in regulating adipogenic differentiation and lipid metabolism in preadipocytes in goats, which is of great significance for uncovering the underlying molecular mechanism of adipocyte differentiation and improving goat meat quality.